THE ROLE OF SPEECH ACTS IN CROSS-CULTURAL COMMUNICATION - Majidova Maftuna Murod qizi (Journal Park Publishing, 2025)
This article explores five key dimensions of how speech acts affect cross-cultural communication. By examining how cultural norms shape language use how directness and politeness vary and how social dynamics influence communicative behavior, we can develop a deeper understanding of why communication sometimes breaks down and how it can be improved.
Keywords: Speech acts, directness, indirectness, individualism and collectivism, direct and indirect speech acts.